Implementasi Virtual Reality Desain Arsitektur Perumahan 3D Sebagai Media Promosi Bisnis Investasi Properti Berbasis Android - Faisyal Rochimul Amri; Cindy Taurusta (Explorer, 2021)
The consumer is the target of all companies to offer the goods and services they have. Various kinds of promotions are carried out in order to attract the interest of consumers so the company can get maximum sales figures. Until now there are still many companies that do not maximize technology for media promotion, especially in the media promotion of residential architecture design. The research entitled "Implementation of Virtual Reality in 3D Housing Architecture Design as a Media for Promoting Android-Based Property Investment Business" was conducted to provide a solution on how to utilize Virtual Reality 3D residential architecture design as a marketing medium for property business entrepreneurs. Researchers hope that the results of this study can provide solutions on how to use Virtual Reality technology to become one of the promotional media, especially the promotion of residential architecture design